2020
DOI: 10.1097/jcn.0000000000000760
|View full text |Cite
|
Sign up to set email alerts
|

Depression as a Risk Factor for Developing Heart Failure

Abstract: Background: The associations of depression with incident heart failure (HF) risk based on epidemiological studies have been inconsistent. Objective: We aimed to quantitatively estimate the relative effect of depression on the development of HF. Methods: We performed a systematic review and meta-analysis of cohort studies published between January 1, 1950, and August 31, 2019, from PubMed, Embase, and the Science Citation Index databases. We selected prospective cohort studies reporting the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(158 reference statements)
1
0
0
Order By: Relevance
“…The effect size observed in our study are comparable to the effect sizes observed in earlier studies regarding the association between other psychological factors, e.g. depression [hazard ratio (HR) (95% CI): 1.2 (1.1–1.4) to 2.8 (1.2–6.4)], 6,8,20 anxiety [HR (95% CI): 1.3 (0.7–2.3) to 2.5 (1.4–4.3)], 6 insomnia [HR (95% CI): 1.3 (1.0–1.6)], 5 or stress‐related disorders [HR (95% CI): 1.4 (1.2–1.6)] 7 and HF, though a few other investigations found no associations between psychosocial factors and HF 8,21 . Our findings thus extend the limited literature on the role of stress, but also other psychosocial factors, in the etiology of HF by studying a severe, objective source of stress in a large bi‐national population with a long follow‐up; this allowed us to perform several sub‐analyses that may contribute to a better understanding of causal mechanisms, and to perform subgroup analyses according to sociodemographic factors.…”
Section: Discussionsupporting
confidence: 88%
“…The effect size observed in our study are comparable to the effect sizes observed in earlier studies regarding the association between other psychological factors, e.g. depression [hazard ratio (HR) (95% CI): 1.2 (1.1–1.4) to 2.8 (1.2–6.4)], 6,8,20 anxiety [HR (95% CI): 1.3 (0.7–2.3) to 2.5 (1.4–4.3)], 6 insomnia [HR (95% CI): 1.3 (1.0–1.6)], 5 or stress‐related disorders [HR (95% CI): 1.4 (1.2–1.6)] 7 and HF, though a few other investigations found no associations between psychosocial factors and HF 8,21 . Our findings thus extend the limited literature on the role of stress, but also other psychosocial factors, in the etiology of HF by studying a severe, objective source of stress in a large bi‐national population with a long follow‐up; this allowed us to perform several sub‐analyses that may contribute to a better understanding of causal mechanisms, and to perform subgroup analyses according to sociodemographic factors.…”
Section: Discussionsupporting
confidence: 88%